Endobronchial ultrasound-guided transbronchial needle aspirate for diagnosis of anaplastic large cell lymphoma of unusual presentation: A case report. (2020) - Sua, Luz F.; Arias, Daniela; Morales, Eliana I.; Bravo, Juan C.; Zúñiga-Restrepo, Valeria; Fernández-Trujillo, Liliana
Abstract: Anaplastic large cell lymphoma (ALCL) is a rare type of non-Hodgkin lymphoma (NHL) originated from mature post thymic T cells. They represent 1–3% of NHL. Different subtypes have been described: Anaplastic lymphoma kinase (ALK)-negative ALCL, ALK-positive ALCL and breast implant-associated ALCL. ALK-positive ALCL affects mainly the young and has better prognosis. We present a case report of an adult woman with AKL-positive ALCL, diagnosed by endobronchial ultrasound-guided transbronchial needle aspirate (EBUS-TBNA). A 59-year-old women with no history of breast implants, was admitted for a four-month low back pain. Initially, the patient was treated for a spondyloarthropathy, but due to persistence of the symptoms, a lumbosacral MRI was performed, showing changes in morphology and signal intensity in the vertebral body of L3, along with edema and a paravertebral collection that affected the left psoas muscle, suggesting granulomatous spondylodiscitis. Chest CT-scan showed mild left pleural effusion, subcarinal and right hiliar adenomegalies. An EBUS-TBNA with ROSE (rapid on-site evaluation) was performed showing positive findings for malignancy, suggestive of hematolymphoid neoplasia. Pathology analysis showed an AKL-positive ALCL. Additionally, a biopsy of paravertebral tissue biopsy was obtained, which was consistent with the nodal sample. Chemotherapy was initiated with the CHOP protocol: cyclophosphamide, hydroxydaunorubicin, vincristine sulfate and prednisone. EBUS-TBNA is a minimally invasive and safe technique for obtaining mediastinal samples. Collaboration with a cytopathologist trained to perform ROSE improves the diagnostic performance.